A simple approach to improve the quality of rice paddy processing wastewater - Neshankine, C.; Kannan, N. (Environmental Science & Engineering Magazine, 2021)
In Sri Lanka, there are 70,000 rice mills performing parboiling of 2.8 million metric tonnes of paddy (rough rice) per year. Rice processing is the country’s largest agro-based sector, producing more output per unit of product than any other industy. In the rice industry, two kinds of products, raw rice and parboiled rice, are produced for consumers. Parboiling is an energy and labour-intensive pre-milling process. Parboiling aims to improve the quality and yield of the rice (head rice). More than 67% of the world’s population consume parboiled rice. Milling of paddy without any pre-treatment is highly susceptible to breakage and loss of minerals and vitamins. The rice mill industry in Sri Lanka uses different types of soaking such as cold, hot, and vacuum soaking. However, most of the milling industry uses the cold soaking process, which takes 48 – 72 hours for the paddy to reach 30% moisture content. The duration is dependent on paddy variety and environmental factors. Wastewater coming from rice mill operations contains high concentrations of organic and inorganic substances, causing significant pollution. The volume of wastewater generated is 0.4 to 0.52 L per kg of paddy processed. In Sri Lanka, many rice industries discharge effluent without any treatment directly into the environment. The release of wastewater to surface water can affect the fertility of fish, another important food source. Moreover, soil respiration and enzyme activities can be inhibited by about 25% – 34%. Research shows such wastewaters have a low concentration of dissolved oxygen (DO) – 0.9 mg/L, a moderate concentrations of chemical oxygen demand (COD) – 630 mg/L, chloride (140 mg/L), total dissolved solids (TDS) – 670 mg/L. Total suspended solids (TSS) – 530 mg/L, and biological oxygen demand (BOD) – 459 mg/L) were much higher than the recommended standards set by the Sri Lanka Standards Institution (SLS) for the discharge of effluent into inland surface waters.